Объяснение:
x+y²=9
x+2y=9
Выражаем х:
х=9-у²
Подставляем в второе уравнение
9-у²+2у=9
-у²+2у =0
у*(-у+2)=0
у=0 или -у+2=0
-у=-2
у=2
х1=9-у²=9-0=9
х2=9-у²=9-4=5
Проверка (9,0) или (5,2)
Проверка 1 (9,0):
9+0=9
9+2*0=9
ответ - являются корнем уравнений
Проверка 2 (5,2):
5+4=9
5+2*2=9
Объяснение:
x+y²=9
x+2y=9
Выражаем х:
х=9-у²
Подставляем в второе уравнение
x+2y=9
9-у²+2у=9
-у²+2у =0
у*(-у+2)=0
у=0 или -у+2=0
-у=-2
у=2
х1=9-у²=9-0=9
х2=9-у²=9-4=5
Проверка (9,0) или (5,2)
Проверка 1 (9,0):
x+y²=9
x+2y=9
9+0=9
9+2*0=9
ответ - являются корнем уравнений
Проверка 2 (5,2):
x+y²=9
x+2y=9
5+4=9
5+2*2=9
ответ - являются корнем уравнений